The role of skirt geometry of dental crowns on the mechanics of failure: Experimental and numerical study - Whitton, A.; Qasim, T.; Ford, Christopher; Hu, X.; Bush, M. (Elsevier Ltd, 2008)
Dental crown structures were modelled using a curved bi-layer system consisting of a brittle glass coating on a compliant polymeric substrate, to illustrate the role of skirt geometry on the mechanics of failure evolution. The geometries of the samples were varied by tapering the skirts of the glass shells in different lengths and thicknesses. The failure of these samples was investigated under single-cycle axial loading tests using an indenter of low elastic modulus. The onset of fracture was observed in situ using a video camera. A relationship between the height and thickness of the taper and the critical load required for a crack to appear in the sample was observed. Margin cracks were observed to propagate from flaws near the margins. Experimental trends suggested that critical loads increased with increasing taper thickness, and decreased with increasing taper length. Finite element modelling was also used to evaluate the stress distribution in the glass coating. Peak maximum principal stresses at the margins decreased with increasing taper thickness, and increased with increasing taper length, consistent with the experimentally determined critical loads. It is concluded that long, narrow tapers should be avoided in order to maximise the load bearing capacity of dental crowns.